2016
DOI: 10.1590/1983-40632016v4641867
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of manipueira to Meloidogyne incognita in soybean1

Abstract: Manipueira, a liquid residue obtained from the cassava industrialization, shows high toxicity to the microbial diversity. This study aimed at evaluating the potential of manipueira applied to the soil to control Meloidogyne incognita in soybean. A completely randomized design, in a 2 x 11 factorial scheme, was used, consisting of two application forms of manipueira (single and two applications), in eleven concentrations (0 %, 10 %, 20 %, 30 %, 40 %, 50 %, 60 %, 70 %, 80 %, 90 % and 100 %), with five replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…The present study revealed findings very different from the reports of Fonseca et al (2016). In their work on soybean in pots of 4.5 L, the fresh mass of the root system showed a 28.11 % rise in response to the application of a single 100 mL dose of manipueira.…”
Section: Effect Of Fertilization On Phytomass Accumulationcontrasting
confidence: 99%
See 1 more Smart Citation
“…The present study revealed findings very different from the reports of Fonseca et al (2016). In their work on soybean in pots of 4.5 L, the fresh mass of the root system showed a 28.11 % rise in response to the application of a single 100 mL dose of manipueira.…”
Section: Effect Of Fertilization On Phytomass Accumulationcontrasting
confidence: 99%
“…The lowest manipueira dose used in this study (436.32 mL) applied to 10 L pots. It became clear that in proportion to the pot volume, this dose was nearly 50 % higher than the one employed by Fonseca et al (2016). Thus, the manipueira doses used in the cowpea crop by organo-mineral fertilization may have been too high and, possibly, damaging to the crop.…”
Section: Effect Of Fertilization On Phytomass Accumulationmentioning
confidence: 98%